Rapid Release of Matrix Metalloproteinase (MMP)-2 by Thrombin in the Rat Aorta: Modulation by Protein Tyrosine Kinase/Phosphatase - Fernandez-Patron, Carlos; Zhang, Yunlong; Radomski, Marek W.; Hollenberg, Morley D.; Davidge, Sandra T. (Thrombosis and Haemostasis, 1999)
Matrix metalloproteinase-2 (MMP-2, gelatinase A) and thrombin contribute to many long-term (patho)physiological processes requiring the proteolytic breakdown of the vascular extracellular matrix (e.g., normal tissue repair, remodeling, tumor invasion, atherosclerosis plaque rupture). Thrombin (10 to 1000 nM, 0.5 to 50 U/ml) induced a rapid secretion of MMP-2 from freshly isolated rat aortic tissue (detectable after 1 min of thrombin exposure). This secretion was mediated by an unidentified thrombin receptor, distinct from the proteinase activated receptors (PAR)-1 and -2. Protein tyrosine kinase/phosphatase activity differentially modulated the basal and the thrombin-induced release of MMP-2. The inhibitors of protein tyrosine kinase, herbymicin A, genistein, and tyrphostin 1288 (1 to 100 μM), enhanced the basal release of MMP-2 but did not affect the thrombin-induced secretion of MMP-2. The inhibitor of phosphotyrosine phosphatases, vanadate (100 μM), selectively inhibited the thrombin-induced, but not the basal, release of MMP-2. Rapid release of vascular MMP-2 by thrombin could contribute to short-term processes where thrombin is involved such as the regulation of platelet aggregation and vascular reactivity. Vascular tyrosine kinase/phosphatase likely modulates this action of thrombin to prevent exaggerated platelet aggregation, thrombosis, and vasospasm.